Interleukins changes in blood of non-ethanol liver damage rats of different sex - Denefil, O.; Bolyukh О. (Journal of Education, Health and Sport, 2022)
Non-alcoholic liver disease is associated with liver injury, such as steatosis, steatohepatitis, fibrosis and cirrhosis. During their development, inflammation is occure and organs damage develops by help of cytokines influences. The intensity of injury depends on sex. The aim of the study was to evaluate changes of interleukins in the blood of male and female rats with hepatosis, hepatitis used by overdrinking of glucose. Material and methods of investigation. The experiments were performed on 60 male and 60 female outbred rats aged from four monthes (start of experiment). Animals were divided into five groups – control 1 (6 monthes old animals), control 2 (8 monthes old animals), glucose 2 monthes (3), glucose 4 monthes (4), and glucose 2+2 monthes (5). Determined in the blood serum Tumor Necrosis Factor Alpha (TNF-α), Interleukin 1 Beta (IL-1β), Interleukin 4 (IL-4), Interleukin 10 (IL-10). Results. In 3, 4 and 5 groups we determined increasing of proinflammatory interleukins. When comparing the results of 5 groups with 3 in male rats, lower values of anti-inflammatory interleukins were noted with a reliably insignificant difference in the content of pro-inflammatory interleukins. Interleukins changes were not detected in rats female between groups 5 and 3.When comparing 3 and 4 groups, an increase in TNF-α and IL-1β, a decrease in IL-4 and IL-10 both in males and in females were determing, which depended on the duration of glucose consumption. When comparing groups 5 and 4 in males rats, only TNF-α decreased, which can be regarded as a decrease in destructive processes when glucose consumption is stopped. In females, we see a decrease in TNF-α and IL-1β, an increase in IL-4 and IL-10, which may indicate a decrease in the effect of glucose or its long-term effect, since the results of groups 3 and 5 in female rats did not differ. Conclusion. An increase in the content of pro-inflammatory interleukins and a decrease in anti-inflammatory interleukins was detected after 2 months, 4 months of glucose use, which is maintained for 2 months after the cessation of its use only 2 months and depends on the duration of glucose use. In males, the inflammatory reaction is more than in females.